2023
DOI: 10.21203/rs.3.rs-2445042/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Childhood trauma, peer victimization, and non-suicidal self-injury among Chinese adolescents: A latent variable mediation analysis

Abstract: Backgrounds: Childhood and peer experiences can influence adolescents' perceptions of interpersonal relationships, which can, in turn, influence their emotional states and behavior patterns. Non-suicidal self-injury (NSSI) is now a common problem behavior among adolescents. The present study examined the role of childhood trauma and peer victimization in adolescents’ NSSI. Methods: A cross-sectional survey was conducted among 1783 adolescents (1464 girls and 318 boys) in the psychiatric outpatient clinics or w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
2
0
0
Order By: Relevance
“…By contrast, all subscale scores on the BIS, except for body touch, were lower in the group with NSSI compared to the group without NSSI. Our findings support the first hypothesis and are consistent with previous research indicating that childhood trauma and alexithymia increase the risk of NSSI (Kautz et al, 2020;Zhao et al, 2023), while bodily investment serves as a protective factor against NSSI (Pérez et al, 2018). In the final prediction model, childhood trauma and body investment were significant predictors of NSSI behavior, which consistent with previous research (Cipriano et al, 2020;Kautz et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, all subscale scores on the BIS, except for body touch, were lower in the group with NSSI compared to the group without NSSI. Our findings support the first hypothesis and are consistent with previous research indicating that childhood trauma and alexithymia increase the risk of NSSI (Kautz et al, 2020;Zhao et al, 2023), while bodily investment serves as a protective factor against NSSI (Pérez et al, 2018). In the final prediction model, childhood trauma and body investment were significant predictors of NSSI behavior, which consistent with previous research (Cipriano et al, 2020;Kautz et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…As a result, the total score for each subscale ranges from 5 to 25. In previous research, the Chinese version of the CTQ-SF demonstrated commendable reliability [34,35]. Cronbach's alpha in our cohort was 0.801.…”
Section: Measurement Toolssupporting
confidence: 57%